2012
DOI: 10.1210/jc.2012-1267
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for Liver Cancer Prevention in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: Metformin appears to be associated with a lower risk of liver cancer in patients with type 2 diabetes. Further investigation, including mechanistic studies, well-designed cohort studies, and possibly controlled trials, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(137 citation statements)
references
References 41 publications
0
125
0
7
Order By: Relevance
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of metformin on liver fat is weak, because of its inability to restore serum adiponectin levels in the short-term [127]. Some preclinical data support an anti-tumorigenic activity of metformin on liver cancer [128], while the demonstration of reduced rates of HCC in humans is limited to retrospective studies [129] and insufficient for evidencebased recommendations. Thiazolidinediones are peroxisome proliferator-activated receptor (PPAR)γ agonists with insulin-sensitising effects.…”
Section: Insulin Sensitisersmentioning
confidence: 99%
“…The effect of metformin on liver fat is weak, because of its inability to restore serum adiponectin levels in the short-term [127] . Some preclinical data support an anti-tumorigenic activity of metformin on liver cancer [128] , while the demonstration of reduced rates of HCC in humans is limited to retrospective studies [129] and insufficient for evidence-based recommendations.Thiazolidinediones are peroxisome proliferator-activated receptor gamma (PPARγ) agonists with insulin-sensitising effects. The PIVENS trial compared low dose pioglitazone vs. vitamin E vs. placebo for 2 years in patients without overt diabetes.…”
mentioning
confidence: 99%